2013
DOI: 10.13102/sociobiology.v60i2.174-182
|View full text |Cite
|
Sign up to set email alerts
|

Arboreal Ant Assemblages Respond Differently to Food Source and Vegetation Physiognomies: a Study in the Brazilian Atlantic Rain Forest

Abstract: This study aimed to analyze assemblages of arboreal ants in different vegetation physiognomies within the Tropical Moist Forest (Atlantic Rain Forest) domain. The study was carried out at the Michelin Ecological Reserve, State of Bahia, Northeast of Brazil. We used sardine (protein resource) and honey (carbohydrate resource) baits to collect ants foraging in three vegetation types: (1) preserved native forest, (2) forest in regeneration (capoeira) with many invasive plants and (3) a mixed agroystem of rubber a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The species richness of arboreal ants sampled in this study (n = 37) can be considered low compared to other studies done in Cerrado or Atlantic Forest, using a similar sampling method. In fragments of Atlantic Forest, for example, species richness may vary from 69 to 153 (Resende et al, 2013;Vasconcelos et al, 2014), whereas in areas of Brazilian savanna (Cerrado) species richness of arboreal ants ranges from 37 to 95 (Ribas et al, 2003;Frizzo et al, 2012). However, for Tropical Dry Forests areas, such as Caatinga, the number of arboreal ants sampled is generally low, ranging from 24 to a maximum of 43 species (Neves et al, 2010c;Neves et al, 2013;Silva et al, 2014), indicating that Caatinga environments, may naturally harbor a smaller ant richness when compared to other environments, probably due to habitat limitations such as drastic variation in resources and conditions during the season and between years (Quesada et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The species richness of arboreal ants sampled in this study (n = 37) can be considered low compared to other studies done in Cerrado or Atlantic Forest, using a similar sampling method. In fragments of Atlantic Forest, for example, species richness may vary from 69 to 153 (Resende et al, 2013;Vasconcelos et al, 2014), whereas in areas of Brazilian savanna (Cerrado) species richness of arboreal ants ranges from 37 to 95 (Ribas et al, 2003;Frizzo et al, 2012). However, for Tropical Dry Forests areas, such as Caatinga, the number of arboreal ants sampled is generally low, ranging from 24 to a maximum of 43 species (Neves et al, 2010c;Neves et al, 2013;Silva et al, 2014), indicating that Caatinga environments, may naturally harbor a smaller ant richness when compared to other environments, probably due to habitat limitations such as drastic variation in resources and conditions during the season and between years (Quesada et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Neoponera apicalis Bahia 1, 3,9,11,14,19,22,23,25,26,31 3,5,7,8,10,13,15,17,20,25,35 5,7,11,14,15,21,22,23,25…”
Section: Species State Referencesmentioning
confidence: 99%
“…Alagoas 30 Bahia 1, 4, 9, 11, 14, 21, 25, 28, 30, 5,7,8,9,12,13,14,20,23,25,29,31,34,35 Espírito Santo 1,13,35 Paraíba 1, 13 Rio Grande do Norte 1…”
Section: Neoponera Venustamentioning
confidence: 99%
“…Environmental heterogeneity can directly influence animal diversity, promoting conditions and resources for a greater coexistence of species (Corrêa et al, 2006, Resende et al, 2011, Silva et al, 2014. In this sense, studies have demonstrated positive relationships between environmental heterogeneity and ant diversity over time, by comparing areas with different phytophysiognomies (Kumar & Mishra, 2008;Resende et al, 2013) or relating vegetation structure to diversity of ants (Santana-Reis & Santos, 2001;Gomes et al, 2010;Vasconcelos et al, 2019).…”
Section: Introductionmentioning
confidence: 99%